サイヒョウセン 「フジ」 ニ ヨル ナンキョク シュウヘン デノ カイジョウ ジュウリョク ソクテイ (ダイ22ジ ナンキョク チイキ カンソクタイ ナツタイ) - 春日, 隆; カスガ, タカシ; 神沼, 克伊; カミヌマ, カツタダ; 瀬川, 爾朗; セガワ, ジロウ; Kasuga, Takashi; Kaminuma, Katsutada; Segawa, Jiro (1982)
P(論文) 第22次南極地域観測隊夏隊による砕氷船「ふじ」船上での海上重力測定は, 1980年11月25日の東京出港から1981年4月20日の帰港までの全航海を通じ, 実施することができた。途中, オーストラリアのフリマントル, 南極・昭和基地, モーリシャスのポートルイス, シンガポールの各寄港中, ラコステG型重力計を用いて, 海上重力計との比較測定も実施した。得られた重力異常値をみると, 東南極の大陸棚では, 氷食地形を除き, 全体としてアイソスタシーが成り立っている。また, グンネラス海堆では, その根もとに-70mgalにも及ぶ負のフリーエア重力異常が観測され, 地下深部に広範囲にわたり密度の大きな物質が存在することが推定される。 Sea gravity measurements on board the icebreaker FUJI during the 22nd Japanese Antarctic Research Expedition conducted from November 1980 to April 1981 were very successful with almost no lack of measurements throughout the cruise. Free air and Bouguer gravity anomalies obtained at the continental shelves of East antarctica show that the crustal structures are isostatic as a whole, except for the glaciated shelves with steep troughs or canyons. The Gunnerus Bank protruding from the Antarctic Continent is associated with free air gravity lows of -70 mgal at the foot of both sides. Existence of these lows indicates that masses of the bathymetric high are isostatically compensated at a great depth. departmental bulletin paper